The use of horizontal force-velocity profile in soccer: a rapid systematic review - Lipcák, A.; Lipková, L.; Kalina, T.; Michaelides, M.; Parpa, K.; Paludo, A. C. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The ability to accelerate and reach high sprinting velocities is crucial to soccer performance. In this context, the horizontal force-velocity profile (H-FVP) has emerged as a tool to evaluate neuromuscular capabilities relevant to sprinting. This rapid review aims to critically describe the application of H-FVP in soccer and summarize the characteristics of the methodologies employed in its measurement and calculation.